2013
DOI: 10.1186/1741-7007-11-105
|View full text |Cite
|
Sign up to set email alerts
|

Precise colocalization of interacting structural and pigmentary elements generates extensive color pattern variation in Phelsumalizards

Abstract: BackgroundColor traits in animals play crucial roles in thermoregulation, photoprotection, camouflage, and visual communication, and are amenable to objective quantification and modeling. However, the extensive variation in non-melanic pigments and structural colors in squamate reptiles has been largely disregarded. Here, we used an integrated approach to investigate the morphological basis and physical mechanisms generating variation in color traits in tropical day geckos of the genus Phelsuma.ResultsCombinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 48 publications
6
150
1
Order By: Relevance
“…6) encountered in the ocelli of M. hrabei is similar to the unidentified blue pigment spectra in chameleons (Teyssier et al, 2015) and the red and green pigment spectra in lizards (Saenko et al, 2013). They, in turn, resemble the Raman spectra of xanthopterin and isoxanthopterin (Saenko et al, 2013;Feng et al, 2001). There is little correspondence with the Raman spectra of melanin, carotene and the simulated spectrum of the ommochrome ommin (Hsiung et al, 2015).…”
Section: Tapetum Structurementioning
confidence: 65%
See 1 more Smart Citation
“…6) encountered in the ocelli of M. hrabei is similar to the unidentified blue pigment spectra in chameleons (Teyssier et al, 2015) and the red and green pigment spectra in lizards (Saenko et al, 2013). They, in turn, resemble the Raman spectra of xanthopterin and isoxanthopterin (Saenko et al, 2013;Feng et al, 2001). There is little correspondence with the Raman spectra of melanin, carotene and the simulated spectrum of the ommochrome ommin (Hsiung et al, 2015).…”
Section: Tapetum Structurementioning
confidence: 65%
“…Raman spectra of pigments from dark blue skin melanophores of panther chameleons (Teyssier et al, 2015) and red skin erythrophores of the lizard Phelsuma lineata (Saenko et al, 2013) exhibit two similar peaks, but the region around 1600 cm −1 is different. The spectrum of melanin from dark-brown chameleon skin melanophores (Teyssier et al, 2015) only shows a single broad peak around 1580 cm…”
Section: Tapetum Structurementioning
confidence: 94%
“…S5 for examples; Kšastle, 1998). In light of recent research on the complex physiologies underlying color production and change in lizards (Saenko et al, 2014;Teyssier et al, 2015), and comprehensive frameworks for the analysis of coloration in natural populations (Kemp et al, 2015), FanThroated Lizards offer a veritable cornucopia to biologists interested in the physiological basis of coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Saenko et al found that the extensive variation in WIREs Nanomedicine and Nanobiotechnology Structural colors color patterns within and among Phelsuma lizard species is generated by complex interactions between chromatophores containing yellow/red pteridine pigments and iridophores producing structural color by constructive interference of light with guanine nanocrystals. 43 These authors showed that the color patterns of Phelsuma always require precise colocalization of different sets of interacting pigmentary and structural elements. For example, yellow and red chromatophores are associated with iridophores with ordered and disordered nanocrystals, respectively.…”
Section: Tunable Structural Colors In Animalsmentioning
confidence: 99%